Phenolic Compound Profiles in Skins of White Wine and Table Grape Cultivars Grown in the National Grape Germplasm Resource Nursery of China - Zhang, M.-X.; Liu, C.-H.; Nan, H.-J.; Li, Z. (South African Journal of Enology and Viticulture, 2016)
The phenolic compound profiles in the skins of white grapes, containing ten wine grape and six table grape cultivars grown in the National Grape Germplasm Resource Nursery at the Zhengzhou Fruit Research Institute of China, were investigated using ultra-high performance liquid chromatography coupled with mass spectrometry (UHPLC-MS/MS). The objective of this study was to evaluate if phenolic compound profiles can be used as indictors to differentiate the quality of wine and table grape cultivars. Significant differences in phenolic compound profiles were observed among these grape cultivar skins. The highest content of total hydroxybenzoic acids, total hydroxycinnamic acids, total flavan-3-ols, total flavones and flavonols and total stilbenes was observed in the skin of the Canada Muscat, Rommel, Kadin parmac, Bacchus and Silvaner cultivars respectively. A great compositional difference was observed among these grape cultivars regarding the individual hydroxycinnamic acids and flavonols. Cluster analysis showed that three table grape cultivars, namely Canada Muscat, Rommel and Kadin parmac, possessed significantly different phenolic compound profiles compared to the other grape cultivars. These results suggested that phenolic compound patterns and contents played important roles in evaluating the quality of table and wine grapes and might provide useful information on grape breeding and winemaking in China.